A Designing an Outsourcing Governance Framework for Strategic IS Management: A Systematic Literature Review Approach - Eman Elnakeep; Sherif Mazen; Iman Helal (Universitas Airlangga, 2026)
Background: Outsourcing has become a critical strategy for organizations aiming to enhance efficiency, reduce costs, and maintain focus on core competencies. Objective: Effective governance remains a significant challenge, particularly in managing long-term and complex outsourcing relationships. Methods: This study proposes a comprehensive governance framework for outsourcing, developed through a systematic literature review (SLR) of models and frameworks published between 2021 and 2025. The proposed framework comprises six interrelated steps that integrate strategic alignment, delivery models, relational and contractual governance, performance monitoring, and innovation enablement. To assess the framework’s practical relevance, a qualitative survey was conducted among outsourcing professionals in Egypt. Results: Results show that over 90% of respondents rated the framework as either good or excellent, confirming its effectiveness and applicability. Conclusion: This study contributes a structured and adaptable governance model for improving the outcomes of outsourcing initiatives and offers a foundation for future empirical validation across sectors and geographies. Keywords: Outsourcing, Governance Model, Practices, Relationships